Muhammad Norshim does UMP proud at National Bestari Chess Challenge - UMP, PNC
Universiti Malaysia Pahang’s (UMP) Muhammad Norshim Mohamed Hashim and his teammates – Nurizzudin Ahmad Hussin, Tuan Shahlan Tuan Safie, Abdullah Muhamad Nawi and Mohd Azizul Hafiz Abdul Sani – did the university proud when they collectively bagged RM50,000 cash after securing the top spot at the National Bestari Chess Challenge held at Persada Johor on January 17.